2017
DOI: 10.1371/journal.pone.0188495
|View full text |Cite
|
Sign up to set email alerts
|

Classical and next generation sequencing approaches unravel Bymovirus diversity in barley crops in France

Abstract: Despite the generalized use of cultivars carrying the rym4 resistance gene, the impact of viral mosaic diseases on winter barleys increased in recent years in France. This change could reflect i) an increased prevalence of the rym4 resistance-breaking pathotype of Barley yellow mosaic virus Y (BaYMV-2), ii) the emergence of rym4 resistance-breaking pathotypes of Barley mild mosaic virus (BaMMV) or iii) the emergence of other viruses. A study was undertaken to determine the distribution and diversity of viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…Samples of barley leaves exhibiting mosaic symptoms collected during field surveys in 2013–2015 (each year from January to April), dried and kept stored over anhydrous calcium chloride at room temperature, were analyzed by high-throughput dsRNA sequencing to evaluate the diversity of bymoviruses in barley 8 (see below). In August 2016, four of these dried leaf samples were taken for total RNA extraction and quality control using RNA blot hybridization analysis with the plant miRNA miR160-specific probe (as detailed in Methods section below).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples of barley leaves exhibiting mosaic symptoms collected during field surveys in 2013–2015 (each year from January to April), dried and kept stored over anhydrous calcium chloride at room temperature, were analyzed by high-throughput dsRNA sequencing to evaluate the diversity of bymoviruses in barley 8 (see below). In August 2016, four of these dried leaf samples were taken for total RNA extraction and quality control using RNA blot hybridization analysis with the plant miRNA miR160-specific probe (as detailed in Methods section below).…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenetic analysis of BaYMV isolates revealed that the 7563 nt RNA1 sequences reconstructed from HYT-37 (deposited in GenBank as MN107377) and HYT-38 (deposited in GenBank as MN107378) exhibit 98.0% pairwise identity (155 SNPs), and are respectively 97.8% and 98.1% identical to the sequence of an isolate collected in France in 2014 (KX117192) 8 that we used for reference-based reconstruction, with SNPs not disrupting a single polyprotein ORF. Among other BaYMV isolates, the RNA1 of HYT-37 is 99.0% identical to that of the KX117208 isolate from Germany, while the RNA1 of HYT-38 is 99.0% identical to that of the KX117195 isolate from France.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As there has been some variations identified in the virus genome to be crucial to the pathogenesis (Habekuß et al 2008;Kanyuka et al 2004;Kühne et al 2003;Rolland et al 2017), future studies on the interaction of particular sites between virus protein and eIF4E could help understanding the mechanism(s) of barley susceptibility to the soil-borne virus disease.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, barley breeding for resistance to the barley yellow mosaic virus disease has mainly relied on alleles of rym4, rym5 or rym1/11 (Kühne 2009), while the diversification and wide distribution of BaYMV/BaMMV in both European (Achon et al 2003;Jezewska and Trzmiel 2009;Rolland et al 2017) and East Asian countries (Chen et al 1999;Hosseini et al 2014;You and Shirako 2013;Zheng et al 1999) remain a constant threat to winter barley production. For example, BaYMV isolates were recently detected in winter barley in Poland and Iran, where the disease was not yet reported (Hosseini et al 2014;Jezewska and Trzmiel 2009).…”
Section: Introductionmentioning
confidence: 99%